Stress-induced production of chemokines by hair follicles regulates the trafficking of dendritic cells in skin - Nagao, Keisuke (2012)
Langerhans cells (LCs) are epidermal dendritic cells with incompletely understood origins that associate with hair follicles for unknown reasons. Here we show that in response to external stress, mouse hair follicles recruited Gr-1(hi) monocyte-derived precursors of LCs whose epidermal entry was dependent on the chemokine receptors CCR2 and CCR6, whereas the chemokine receptor CCR8 inhibited the recruitment of LCs. Distinct hair-follicle regions had differences in their expression of ligands for CCR2 and CCR6. The isthmus expressed the chemokine CCL2; the infundibulum expressed the chemokine CCL20; and keratinocytes in the bulge produced the chemokine CCL8, which is the ligand for CCR8. Thus, distinct hair-follicle keratinocyte subpopulations promoted or inhibited repopulation with LCs via differences in chemokine production, a feature also noted in humans. Pre-LCs failed to enter hairless skin in mice or humans, which establishes hair follicles as portals for LCs.